SCHIZORIZA controls an asymmetric cell division and restricts epidermal identity in the Arabidopsis root. - Mylona, P; Linstead, P; Martienssen, R; Dolan, L (2002)
The primary root of Arabidopsis has a simple cellular organisation. The fixed radial cell pattern results from stereotypical cell divisions that occur in the meristem. Here we describe the characterisation of schizoriza (scz), a mutant with defective radial patterning. In scz mutants, the subepidermal layer (ground tissue) develops root hairs. Root hairs normally only form on epidermal cells of wild-type plants. Moreover, extra periclinal divisions (new wall parallel to surface of the root) occur in the scz root resulting in the formation of supernumerary layers in the ground tissue. Both scarecrow (scr) and short root (shr) suppress the extra periclinal divisions characteristic of scz mutant roots. This results in the formation of a single layered ground tissue in the double mutants. Cells of this layer develop root hairs, indicating that mis-specification of the ground tissue in scz mutants is uncoupled to the cell division defect. This suggests that during the development of the ground tissue SCZ has two distinct roles: (1) it acts as a suppressor of epidermal fate in the ground tissue, and (2) it is required to repress periclinal divisions in the meristem. It may act in the same pathway as SCR and SHR.